Smartphone and App Implementations that Improve Productivity - Nisar, Tahir M. (Berlin ; Boston : De Gruyter, 2019)
The introduction of digital applications into businesses has revolutionized the way employees and managers carry out their jobs while also benefiting them socially. Smartphone and App Implementations that Improve Productivity looks at the benefits of apps in the workplace and introduces academic perspectives that link prospective advantages with practical commercial examples. The analysis is structured into chapters that include real world application while at the same time critically assess implied benefits of the new app technology and draw out the main findings and conclusions. Tahir M. Nisar brings into focus the emerging role of digital applications and big data in enterprise decision making. Readers will learn how companies can achieve more efficiency and effectiveness in their business operations through new types of organizational design strategies and mechanisms of employee mobility and work-life balance that draw on digital apps.
Frontmatter -- Acknowledgments -- Contents -- Preface -- Chapter 1: New Innovative Business Services -- Chapter 2: Mobile Communications and Big Data -- Chapter 3: Management of Enterprise Resource Systems -- Chapter 4: Technology and a Firm's Capabilities -- Chapter 5: Management Processes and Decision Making -- Chapter 6: Apps and Performance Outcomes -- Chapter 7: Mobility and Work-Life Balance -- Chapter 8: New Digital Markets and Emerging Business Models -- Chapter 9: The Case for Business Issued Smartphones -- Chapter 10: Maximizing Productivity in the Smartphone Enabled Workplace -- Bibliography -- Index
Mode of access: Internet via World Wide Web.
In English.
Description based on online resource; title from PDF title page (publisher's Web site, viewed 06. Apr 2020)
Keywords: Analytics; Big data; Digital app; Digital applications; Digital marketing; Smartphone; COMPUTERS / Hardware / Mobile Devices